Gingival esthetics: an orthodontic and periodontal approach - Máyra Reis Seixas; Roberto Amarante Costa-Pinto; Telma Martins de Araújo (Dental Press Editora, 2012)
INTRODUCTION: Currently, people's esthetic requirements and expectations have increased substantially. Therefore, dentists have been seeking ways to provide excellent treatment results which, consequently, increasingly require a well organized transdisciplinary approach. The link between orthodontics and periodontics became evident from the moment professionals began to understand the biology of tooth movement. As regards smile esthetics, however, such cooperation is now essential. OBJECTIVE: To show clinically how and when orthodontists and periodontists should work jointly to enhance smile esthetics based on the display and harmony of the gingival contour. INTRODUÇÃO: nos dias atuais, as expectativas e exigências estéticas das pessoas têm aumentado substancialmente. Por isso, a Odontologia vem buscando maneiras de oferecer tratamentos com resultados excelentes e, consequentemente, necessita trabalhar, cada vez mais, de modo transdisciplinar. A inter-relação da Ortodontia com a Periodontia é evidente desde quando se compreendeu a biologia da movimentação dentária; contudo, em se tratando de estética do sorriso, tornou-se fundamental. OBJETIVO: evidenciar, clinicamente, como e quando a Ortodontia e a Periodontia devem trabalhar de modo integrado para a obtenção de sorrisos mais estéticos, considerando-se a exposição e a harmonia do contorno gengival.